2012
DOI: 10.1152/physiol.00003.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling and Maintenance of Homeostasis in the Intestinal Epithelium

Abstract: Homeostasis of the rapidly renewing intestinal epithelium depends on a balance between cell proliferation and loss. Indian hedgehog (Ihh) acts as a negative feedback signal in this dynamic equilibrium. We discuss recent evidence that Ihh may be one of the key epithelial signals that indicates epithelial integrity to the underlying mesenchyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 43 publications
0
69
0
1
Order By: Relevance
“…These data suggest that subepithelial PDGFR␣ ϩ cells in murine colonic mucosa may be targets for Indian hedgehog, which is released from the colonic epithelium (42). Hedgehog signaling has an important role in maintaining homeostasis in the intestinal mucosa, but questions about its role remain unanswered (8). Finding a new target for hedgehog signaling might provide greater insight into the role of this pathway.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These data suggest that subepithelial PDGFR␣ ϩ cells in murine colonic mucosa may be targets for Indian hedgehog, which is released from the colonic epithelium (42). Hedgehog signaling has an important role in maintaining homeostasis in the intestinal mucosa, but questions about its role remain unanswered (8). Finding a new target for hedgehog signaling might provide greater insight into the role of this pathway.…”
Section: Discussionmentioning
confidence: 94%
“…Htr3a and Htr3b expressions were much lower in PDGFR␣ ϩ cells than in other mucosal cells. Recently, mesenchymal PDGFR␣ ϩ cells in embryonic small intestine were reported to express hedgehog signaling molecules, Patched1 and the glioblastoma transcription factor 1 (Gli1) (44) and hedgehog signaling is expressed in colonic mesenchymal cells and contribute to maintenance of mucosal homeostasis (42,8). Therefore we probed the expression of two hedgehog signaling molecules (Ptch1 and Gli1).…”
Section: G829 Colonic Subepithelial Pdgfr␣ ϩ Cellsmentioning
confidence: 99%
“…In contrast, in the intestine signaling is uniquely from the differentiated epithelial cells to the underlying mesenchyme. Here Hedgehog signaling regulates survival and expansion of the mesenchyme and in fact negatively regulates epithelial precursor cell proliferation (11).…”
Section: Signaling Pathways Involved In Esophageal Morphogenesismentioning
confidence: 99%
“…Thus Bmp4 is required for proper airway development after the initial specification of the tracheal primordium. The importance of Bmp4 in airway development may explain why the airways fail to develop properly in Shh-mutant mice since Bmp4 is one of the key mesenchymal targets of Hedgehog-Foxf1/Foxf2 signaling in the esophagus (42) and the intestine (11).…”
Section: The Morphogenetic Signaling Network Responsible For Gutairwamentioning
confidence: 99%
“…33 Interestingly, it has been shown that together with a barrier-promoting effect, activation of the SHH pathway favors the immune quiescence of BBB by reducing the expression of pro-inflammatory cytokines and leukocyte transmigration. 33 In the gut, SHH signaling is necessary for the formation of villi during development and has homeostatic functions in the adult 34,35 indeed Hedgehog ligands, produced mainly by the epithelium, act on mesenchymal cells (smooth muscle cells, myofibroblast-like cells and pericytes located in the lamina propria) and they function as signals to assess epithelial barrier integrity. Our new data suggest an involvement of the SHH pathway also in the maintenance of the GVB but further investigation is required.…”
mentioning
confidence: 99%